Partial Least Squares Regression Analysis Between Body Mass Index, Abdominal Circumference, Hip Circumference, Hemoglobin, Body Composition, Uric Acid, Blood Sugar, Hemoglobin and Hematocrit with Face Analyzer in Adults - Sukmawati Tansil Tan; Farell Christian; Cindy Christella Chandra; Yohanes Firmansyah (Universitas Malahayati Lampung, 2024)
ABSTRACT Skin is an important aspect of the human body. Many factors may influence skin health and its characteristics, including physiological and metabolic conditions such as obesity, blood sugar, hemoglobin and hematocrit, and uric acid. To establish a correlation between physiological and metabolic health parameters with skin-face analysis (roughness and wrinkles). This research was conducted in Kalam Kudus Foundation, West Jakarta, targeting individuals ≥17 years old, both men and women, following the inclusion and exclusion criteria. Skin health parameters used were roughness and wrinkles. The metabolic parameters studied were body mass index (BMI), waist circumference (WC), hip circumference (HC), body composition, blood sugar, hemoglobin (Hb), hematocrit (Ht), and uric acid. Our research shows negative coefficient results of BMI (-0,076 and –0,059), WC (-0,844 and -0,795), Hb (-0,069 and -0,074), Ht (-0,112 and -0,161), and uric acid (-0,155 and -0,170) with skin roughness and wrinkle. Other parameters such as HC (0,294 and 0,323), blood glucose (0,141 and 0,058), total body fat mass (0,321 and 0,345), visceral fat (0,234 and 0,203), total subcutaneous fat (0,319 and 0,391), and total muscle mass (0,725 and 0,890) result in a positive coefficient with skin roughness and wrinkle. An increase in BMI, WC, Hb, Ht, and uric acid is associated with better skin roughness and wrinkles while higher hip circumference, total body fat mass, visceral fat, total subcutaneous fat, total muscle mass, and blood sugar may worsen the skin condition. Keywords: Obesity, Blood Sugar, Hemoglobin, Hematocrit, Uric Acid, Skin Roughness, Wrinkles